Discrepancies between paper and practice in policy implementation: Tajikistan's property rights and customary claims to land and water - Frederike Klümper; Insa Theesfeld; Thomas Herzfeld (Land Use Policy, 2018)
Property rights granted by land and water policies are not always identical with the claims – meaning perceived rights - people base their actions on. A high discrepancy between both resembles an ineffective policy implementation and bears the risk of unsustainable decision-making. Furthermore, perceived rights to land and its corresponding resource water can vary significantly. In this paper, we operationalize the property rights concepts and empirically assess, by specifying and quantifying, the difference between property rights and farmers' customary claims to both, land and water resources. With regard to land, actors tend to base their decisions on customary claims, and override property rights. In contrast, regarding water, we find that the full benefits of property rights granted by a policy reform are often not recognized. Whereas in the first case political control and monitoring mechanisms seems to fail, in the latter a lack of information sharing let the farmers not exploit their full investment potential.
Keywords: 630; land and water use; policy reform; property rights; customary claims; Tajikistan